Composite gel system ceramsite foam concrete and preparation method thereof

Through the optimization of the components and preparation method of the composite cementitious system, the problems of low strength and easy cracking of expanded clay foam concrete were solved, its forming performance and compressive strength were improved, its tensile strength and impact resistance were enhanced, and the preparation process was simplified.

CN120647292APending Publication Date: 2025-09-16SICHUAN YONGJING INVESTMENT GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510701492.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing expanded clay foam concrete has the problems of low strength and easy cracking and collapse, making it difficult to improve its mechanical strength and shrinkage resistance while maintaining a low bulk density and thermal conductivity.

Method used

A composite gelling system is adopted, including gel material, river sand, shale ceramsite, polypropylene fiber, cellulose, latex powder, water reducer and modified foaming agent, and a high-density and stable foam structure is formed by optimizing the component ratio and preparation method.

Benefits of technology

It improves the molding performance and compressive strength of ceramsite foam concrete, enhances the tensile strength and impact resistance, improves the toughness and fluidity, reduces the drying shrinkage, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120647292A_ABST
    Figure CN120647292A_ABST
Patent Text Reader

Abstract

The invention discloses composite gel system ceramsite foam concrete and a preparation method thereof, and relates to the technical field of building materials, the ceramsite foam concrete comprises the following components by weight: 300-400 parts of a gel material, 30-40 parts of river sand, 100-110 parts of shale ceramsite, 0.3-0.4 part of polypropylene fiber, 6-8 parts of cellulose, 6-8 parts of latex powder, 6-8 parts of a water reducer, 1-5 parts of a foaming agent, and 80-100 parts of water. The invention also provides a preparation method of the ceramsite foam concrete. The formability and compressive strength of the prepared composite gel system ceramsite foam concrete are improved, and the problems that ceramsite foam concrete is low in strength and prone to cracking and mold collapse are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a composite gelling system ceramsite foam concrete and a preparation method thereof. Background Art

[0002] Ceramic aggregate is a lightweight aggregate that, after high-temperature calcination, exhibits numerous advantages, including lightness, high strength, fire resistance, non-toxicity, and sound and energy absorption. After decades of development and application in China, it has become one of the best aggregates for energy-saving materials. Compared to natural minerals, ceramsite has a more complex composition. The surface of ceramsite is reactive, allowing it to chemically react with cement, thereby improving the strength and stability of concrete. Furthermore, the microtubule system within ceramsite creates a "micro-pumping" effect, effectively improving the compactness of concrete and promoting the strength and durability of foamed concrete. In actual production, ceramsite has a low bulk density and often floats during the vibrating and forming process, which can negatively impact the strength of concrete. The addition of a series of thickeners can effectively mitigate this surface floating of ceramsite in foamed concrete, thereby optimizing aggregate distribution and thus affecting strength. This makes ceramsite foamed concrete more suitable for the combined requirements of building structures and energy conservation. Overall, research on either single ceramsite concrete or foamed concrete is relatively mature both domestically and internationally, but further research on ceramsite foamed concrete remains limited.

[0003] Using ceramsite as a lightweight aggregate in foamed concrete not only ensures lightweight insulation but also enhances new properties like shrinkage resistance. However, this still presents drawbacks such as low strength and cracking and mold collapse. Therefore, further research is needed to optimize the mix ratio of ceramsite foamed concrete, aiming to improve mechanical strength and shrinkage resistance while maintaining a low bulk density and thermal conductivity. Summary of the Invention

[0004] In response to the above-mentioned deficiencies in the prior art, the present invention provides a composite cementitious system ceramsite foam concrete and a preparation method thereof. The preparation method of the composite cementitious system ceramsite foam concrete is simple, and the molding performance and compressive strength of the prepared composite cementitious system ceramsite foam concrete are improved, effectively solving the problems of low strength and easy cracking and collapse of ceramsite foam concrete.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention to solve the technical problem is: providing a composite gelling system ceramsite foam concrete, comprising the following components by weight: 300-400 parts of gel material, 30-40 parts of river sand, 100-110 parts of shale ceramsite, 0.3-0.4 parts of polypropylene fiber, 6-8 parts of cellulose, 6-8 parts of latex powder, 6-8 parts of water reducer, 1-5 parts of modified foaming agent and 80-100 parts of water.

[0006] Furthermore, the composite gelling system ceramsite foam concrete includes the following components in parts by weight: 320 parts of gel material, 35 parts of river sand, 105 parts of shale ceramsite, 0.35 parts of polypropylene fiber, 7 parts of cellulose, 7 parts of latex powder, 7 parts of water reducer, 1-5 parts of modified foaming agent and 90 parts of water.

[0007] Furthermore, the gel material comprises the following components in parts by weight: 50-55 parts of pozzolanic silicate cement, 5-10 parts of rapid-hardening sulphoaluminate cement, 15-25 parts of microspheres and 15-25 parts of lithium mineral powder.

[0008] Furthermore, the gel material comprises the following components in parts by weight: 52 parts of pozzolanic silicate cement, 8 parts of rapid-hardening sulphoaluminate cement, 20 parts of microspheres and 20 parts of lithium mineral powder.

[0009] Furthermore, the above-mentioned pozzolanic silicate cement includes the following components in parts by weight: 62-67 parts of calcium oxide, 20-24 parts of silicon dioxide, 4-7 parts of aluminum oxide, 3-6 parts of iron oxide, 1-2 parts of magnesium oxide, 1-2 parts of silicon trioxide, 1-2 parts of disodium oxide, 1-2 parts of potassium oxide, 1-2 parts of titanium dioxide, and 1-2 parts of phosphorus pentoxide.

[0010] Furthermore, the above-mentioned pozzolanic silicate cement includes the following components in parts by weight: 62-67 parts of calcium oxide, 22 parts of silicon dioxide, 5 parts of aluminum oxide, 5 parts of iron oxide, 2 parts of magnesium oxide, 2 parts of silicon trioxide, 1 part of disodium oxide, 1 part of potassium oxide, 1 part of titanium dioxide, and 1 part of phosphorus pentoxide.

[0011] Furthermore, the rapid-hardening sulphoaluminate cement comprises the following components in parts by weight: 20-30 parts of aluminium oxide, 40-50 parts of calcium oxide, 10-20 parts of silicon dioxide, 5-10 parts of sulfur trioxide and 1-2 parts of magnesium oxide.

[0012] Furthermore, the rapid-hardening sulphoaluminate cement comprises the following components in parts by weight: 28 parts of aluminium oxide, 47 parts of calcium oxide, 12 parts of silicon dioxide, 10 parts of sulfur trioxide and 1 part of magnesium oxide.

[0013] Furthermore, the particle size of the microbeads is 0.1-5 μm.

[0014] Furthermore, the microbeads include the following components in parts by weight: 50-60 parts of silicon dioxide, 3-8 parts of calcium oxide, 1-3 parts of magnesium oxide, 5-10 parts of ferric oxide, 20-30 parts of aluminum oxide, 1-3 parts of sodium oxide and 1-5 parts of potassium oxide.

[0015] Furthermore, the microbeads include the following components in parts by weight: 56 parts of silicon dioxide, 5 parts of calcium oxide, 1 part of magnesium oxide, 5 parts of ferric oxide, 27 parts of aluminum oxide, 1 part of sodium oxide and 3 parts of potassium oxide.

[0016] Furthermore, the lithium ore powder comprises the following components in parts by weight: 0.3-0.4 parts of lithium oxide, 60-70 parts of aluminum sulfate, 10-20 parts of calcium sulfate, 1-3 parts of ferrous sulfate, 1-3 parts of magnesium sulfate, 1-3 parts of potassium sulfate and 0.5-1 parts of sodium sulfate.

[0017] Furthermore, the lithium ore powder comprises the following components in parts by weight: 0.3-0.4 parts of lithium oxide, 60-70 parts of aluminum sulfate, 10-20 parts of calcium sulfate, 1-3 parts of ferrous sulfate, 1-3 parts of magnesium sulfate, 1-3 parts of potassium sulfate and 0.5-1 parts of sodium sulfate.

[0018] Furthermore, the lithium ore powder comprises the following components in parts by weight: 0.35 parts of lithium oxide, 62 parts of aluminum sulfate, 12 parts of calcium sulfate, 2 parts of ferrous sulfate, 1 part of magnesium sulfate, 1 part of potassium sulfate and 0.7 parts of sodium sulfate.

[0019] Furthermore, the river sand is a fine aggregate, and the shale ceramsite is a lightweight aggregate.

[0020] Furthermore, the diameter of the shale ceramsite is 1.5-2 cm, and the natural bulk density ranges from 420-450 kg / m 3 , the pre-wetting degree is 50%.

[0021] Furthermore, the length of the polypropylene fiber is 12 mm.

[0022] Furthermore, the water reducer is a polycarboxylic acid-type high-performance water reducer with a water reduction rate exceeding 30%.

[0023] Furthermore, the foaming agent comprises the following components in parts by weight: 0.01 parts of gum arabic and 1 part of micron protein cement foaming agent.

[0024] Furthermore, the water-to-cement ratio of the composite cementitious system ceramsite foam concrete is 0.28-0.4.

[0025] Furthermore, the water-cement ratio of the composite cementitious system ceramsite foam concrete is 0.28.

[0026] Furthermore, the preparation method of the composite gelling system ceramsite foam concrete is characterized by comprising the following steps: S1. Mix the gel material, river sand and shale ceramsite evenly to obtain a premixed dry material; S2. Mix the cellulose, latex powder and 1 / 2 of the water, add them to the premixed dry material obtained in step S1 and stir, then add the remaining water and stir to obtain a mixture; S3. Add a water reducer to the mixture obtained in step S2, and then add polypropylene fibers. After the slurry is fluidized, continue stirring until the polypropylene fibers are evenly dispersed, thereby obtaining a gelling material mixed slurry; S4. Dilute the modified foaming agent with water to prepare foam, add the foam to the cementitious material mixed slurry obtained in step S3, stir rapidly until the foam disappears, and then let it stand and cure to a corresponding age to obtain composite cementitious system ceramsite foam concrete.

[0027] Further, in step S1, stirring is performed for 50-70 seconds.

[0028] Further, stirring was performed for 60 seconds.

[0029] Furthermore, in step S2, the premixed dry material obtained in step S1 is added and stirred for 20-40 seconds.

[0030] Further, add the premixed dry material obtained in step S1 and stir for 30 seconds.

[0031] Further, in step S3, stirring is continued for 1-3 minutes.

[0032] Further, in step S3, stirring is continued for 2 minutes.

[0033] Furthermore, in step S4, the gas and liquid valves of the foaming agent are opened, and the modified foaming agent is used to prepare foam by physical foaming under air pressure, and the input gas and liquid flow rates are manually adjusted to stabilize the foam quality.

[0034] Furthermore, the mass ratio of the modified foaming agent to water is 1-2:35-45.

[0035] Furthermore, the mass ratio of the modified foaming agent to water is 1:40.

[0036] Furthermore, the mixture is allowed to stand for 20-30 hours at a temperature of 15-25° C. and a humidity of 93-97%.

[0037] Furthermore, the mixture was allowed to stand for 24 hours at a temperature of 20°C and a humidity of 95%.

[0038] In summary, the present invention has the following beneficial effects: 1. The present invention replaces part of the cement by incorporating silica fume and lithium ore powder into concrete, improving the compactness and strength of the concrete and contributing to its durability. Microbeads have the advantages of high activity, continuous particle size distribution, large surface area, and good inter-particle filling. Their structural distribution has certain advantages in concrete. Adding microbeads in appropriate amounts can reduce water consumption and concrete viscosity, thereby increasing its workability. River sand is used as fine aggregate, and shale ceramsite is used as lightweight aggregate, which can form a skeleton and increase strength. The pre-wetted ceramsite particles produce moisture changes within the particles, effectively reducing drying shrinkage. Polypropylene fibers have a high elastic modulus. When cracks form within the concrete, the fibers can shuttle through the cracks and withstand tensile stress, thereby increasing the tensile strength of the concrete and effectively enhancing its volume stability. The random distribution of polypropylene fibers can also improve the toughness and impact resistance of the concrete. Latex powder, cellulose, and a water-reducing agent can thicken and retain water, resist floating, and improve fluidity. The present invention also provides an optimal ratio between the components, enhancing the performance of composite cementitious system ceramsite foam concrete.

[0039] 2. By modifying the foaming agent, in addition to enhancing the foaming ability, the adhesion between foams can be improved, and the thickness of the foam wall can be increased to improve the foam stability.

[0040] 3. The preparation method of the composite gelling system ceramsite foam concrete provided by the present invention is simple, which greatly saves time and cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the result diagram of the effect of different foam stabilizer dosage on the compressive strength of ceramsite foam concrete; Figure 2 This is the result diagram of the effect of different microbead dosage on the moisture content and absolute dry density of ceramsite foam concrete; Figure 3 This is the result diagram of the effect of different microbead dosage on the mechanical strength and softening coefficient of ceramsite foam concrete; Figure 4 This is the result diagram of the effect of different rapid-hardening sulphoaluminate cement dosages on the moisture content and absolute dry density of ceramsite foam concrete; Figure 5 This is the result diagram of the effect of different rapid-hardening sulphoaluminate cement dosage on the mechanical strength and softening coefficient of ceramsite foam concrete; Figure 6 This is the result diagram of the effect of different lithium mineral powder dosage on the moisture content and absolute dry density of ceramsite foam concrete; Figure 7 This is the result diagram of the effect of different lithium mineral powder dosage on the mechanical strength and softening coefficient of ceramsite foam concrete; Figure 8 This is a comparison of the CaO / SiO2 content of expanded clay foam concrete with different composite gel systems. DETAILED DESCRIPTION

[0042] The present invention will be further described below with reference to the embodiments and drawings, but they do not limit the present invention.

[0043] Example 1 A composite gelling system ceramsite foam concrete comprises the following components in parts by weight: 320 parts of gel material, 35 parts of river sand, 105 parts of shale ceramsite, 0.35 parts of polypropylene fiber, 7 parts of cellulose, 7 parts of latex powder, 7 parts of water reducing agent, 3 parts of modified foaming agent and 90 parts of water.

[0044] The gel material comprises the following components in parts by weight: 52 parts of pozzolanic silicate cement, 8 parts of rapid-hardening sulphoaluminate cement, 20 parts of microspheres and 20 parts of lithium mineral powder.

[0045] The preparation method of the composite gelling system ceramsite foam concrete comprises the following steps: S1. Mix pozzolanic Portland cement, rapid-hardening sulphoaluminate cement, microspheres, lithium ore powder, river sand and shale ceramsite for 60 seconds to obtain a premixed dry material; S2. Mix cellulose, latex powder and 1 / 2 of the water, add to the premixed dry material obtained in step S1 and stir for 30 seconds, then add the remaining water and stir to obtain a mixture; S3. Add a water reducer to the mixture obtained in step S2, and then add polypropylene fibers. After the slurry is fluidized, continue stirring for 2 minutes until the polypropylene fibers are evenly dispersed, thereby obtaining a gelling material mixed slurry; S4. Dilute the modified foaming agent with water at a ratio of 1:40, open the gas-liquid valves of the foaming agent, prepare foam by physical foaming under air pressure using the modified foaming agent, manually adjust the input gas-liquid flow rate to stabilize the foam quality, add the foam to the cementitious material mixed slurry obtained in step S3, stir rapidly until the foam disappears, and then stand at a temperature of 20° C. and a humidity of 95% for 24 hours, and cure to the corresponding age to obtain a composite cementitious system ceramsite foam concrete.

[0046] Example 2 A composite gelling system ceramsite foam concrete comprises the following components in parts by weight: 300 parts of gel material, 30 parts of river sand, 100 parts of shale ceramsite, 0.3 parts of polypropylene fiber, 6 parts of cellulose, 6 parts of latex powder, 6 parts of water reducing agent, 1 part of modified foaming agent and 80 parts of water.

[0047] The gel material comprises the following components in parts by weight: 50 parts of pozzolanic silicate cement, 5 parts of rapid-hardening sulphoaluminate cement, 15 parts of microspheres and 15 parts of lithium mineral powder.

[0048] The preparation method of the composite gelling system ceramsite foam concrete comprises the following steps: S1. Stir pozzolanic Portland cement, rapid-hardening sulphoaluminate cement, microspheres, lithium ore powder, river sand and shale ceramsite for 50 seconds to obtain a premixed dry material; S2. Mix the cellulose, latex powder, and 1 / 2 of the water, add them to the premixed dry material obtained in step S1, and stir for 20 seconds. Then, add the remaining water and stir until uniform, to obtain a mixture. S3. Add a water reducer to the mixture obtained in step S2, and then add polypropylene fibers. After the slurry is fluidized, continue stirring for 1 minute until the polypropylene fibers are evenly dispersed, thereby obtaining a gelling material mixed slurry; S4. Dilute the modified foaming agent with water in a ratio of 1:35, open the gas-liquid valves of the foaming agent, prepare foam by physical foaming under air pressure using the modified foaming agent, manually adjust the input gas-liquid flow rate to stabilize the foam quality, add the foam to the cementitious material mixed slurry obtained in step S3, stir rapidly until the foam disappears, and then stand at a temperature of 15° C. and a humidity of 93% for 20 hours, and cure to the corresponding age to obtain a composite cementitious system ceramsite foam concrete.

[0049] Example 3 A composite gelling system ceramsite foam concrete comprises the following components in parts by weight: 400 parts of gel material, 40 parts of river sand, 110 parts of shale ceramsite, 0.4 parts of polypropylene fiber, 8 parts of cellulose, 8 parts of latex powder, 8 parts of water reducing agent, 5 parts of modified foaming agent and 100 parts of water.

[0050] The gel material comprises the following components in parts by weight: 60 parts of pozzolanic silicate cement, 10 parts of rapid-hardening sulphoaluminate cement, 25 parts of microspheres and 25 parts of lithium mineral powder.

[0051] The preparation method of the composite gelling system ceramsite foam concrete comprises the following steps: S1. Mix the pozzolanic Portland cement, rapid-hardening sulphoaluminate cement, microspheres, lithium ore powder, river sand and shale ceramsite for 70 seconds to obtain a premixed dry material; S2. Mix the cellulose, latex powder, and 1 / 2 of the water, add the mixture to the premixed dry material obtained in step S1, and stir for 40 seconds. Then, add the remaining water and stir to obtain a mixture. S3. Add a water reducer to the mixture obtained in step S2, and then add polypropylene fibers. After the slurry is fluidized, continue stirring for 3 minutes until the polypropylene fibers are evenly dispersed, thereby obtaining a gelling material mixed slurry; S4. Dilute the modified foaming agent with water in a ratio of 2:45, open the gas-liquid valves of the foaming agent, prepare foam by physical foaming under air pressure using the modified foaming agent, manually adjust the input gas-liquid flow rate to stabilize the foam quality, add the foam to the cementitious material mixed slurry obtained in step S3, stir rapidly until the foam disappears, and then stand at a temperature of 25° C. and a humidity of 97% for 30 hours, and cure to the corresponding age to obtain a composite cementitious system ceramsite foam concrete.

[0052] Test Example 1 In order to explore the effect of different dosages of foam stabilizer on the compressive strength of composite cementitious system ceramsite foam concrete, the dosage of gum arabic was set to 0%, 0.1% and 2%, and the compressive strength test was carried out. The results are as follows: Figure 1 shown.

[0053] Depend on Figure 1 As can be seen, with increasing gum arabic content, the compressive strength of ceramsite foam concrete first increases and then decreases. At a gum arabic content of 0.1%, the 28-day compressive strength reaches its highest, 1.90 MPa; at a 2% content, the 28-day compressive strength decreases. This is primarily due to the excessive addition of a foam stabilizer, which increases the viscosity of the micronized protein foaming agent, hindering foaming. Therefore, a 0.1% foam stabilizer content ensures both a good foaming ratio and enhanced foam stability. However, as the content increases, the mother liquor viscosity increases, increasing the gravity required for foaming, thereby reducing the foaming ratio and stability. This leads to reduced dispersion of the gum arabic in the slurry, a deterioration of the cell structure, and ultimately a decrease in compressive strength.

[0054] Test Example 2 In order to explore the effect of micro-bead content on the performance of ceramsite foam concrete, the moisture content, absolute dry density, compressive strength and softening coefficient of ceramsite foam concrete with micro-bead content of 0%, 10%, 20% and 30% were tested respectively. The results of the influence of different micro-bead content on moisture content and absolute dry density are shown as follows: Figure 2 The results of the effects of different microsphere dosages on mechanical strength and softening coefficient are shown in Figure 3 shown.

[0055] Depend on Figure 2 As can be seen, as the microbead content increases from 0% to 30%, the moisture content of ceramsite foam concrete decreases, but the dry density does not change significantly. The main reasons for the former are mainly due to two factors: first, the "micro-aggregate effect" of the microbeads in the cement paste, which acts as micro-aggregate to fill the pores of the thickened paste; second, the "rolling ball effect", which reduces the internal friction of the mixed paste and improves the hydration efficiency, promoting the density of the concrete matrix, thereby reducing the moisture content.

[0056] Depend on Figure 3As can be seen, the compressive strength of ceramsite foam concrete decreases at 3 days with increasing microbead content. When the microbead content reaches 30%, the 3-day compressive strength decreases by 27%, and the 7-day compressive strength decreases insignificantly. The 28-day compressive strength increases first and then decreases with increasing microbead content. When the microbead content increases from 10% to 20%, the 28-day compressive strength gradually increases and reaches a maximum of 3.4 MPa. When the content continues to increase to 30%, the mechanical strength decreases. The softening coefficient increases first and then decreases with increasing microbead content, reaching a maximum of 0.97 at a 20% content and showing no significant increase at 30%.

[0057] In summary, the introduction of microspheres likely reduced the amount of pozzolanic Portland cement involved in the hydration reaction, resulting in a lower concentration of hydrated calcium silicate and calcium aluminate, and a looser structure in the resulting cement hardened stone, leading to a decrease in early compressive strength. Furthermore, in the early stages of the hydration reaction, the microspheres primarily served as "microaggregates" and did not effectively participate in the hydration process. After 7 days, the potential activity of the microspheres began to play a role. Under alkaline conditions, the microspheres utilized CH in the concrete, transforming it into CSH gel, which enhanced the hardness of the cement paste. This increased the density of the concrete matrix, filling early defects and resulting in a significant increase in compressive strength after 28 days. Furthermore, the increase in the softening coefficient may be attributed to the "microaggregate" effect of the microspheres and secondary hydration, which refined the concrete pores, reduced the number of large and interconnected pores in the pore structure, lowered the moisture content, increased the softening coefficient, and enhanced the water resistance of the ceramsite foam concrete.

[0058] Test Example 3 In order to explore the effect of rapid hardening sulphoaluminate cement content on the performance of ceramsite foam concrete, the moisture content and absolute dry density of ceramsite foam concrete with rapid hardening sulphoaluminate cement content of 0%, 4%, 8% and 12% were tested respectively. The results are as follows: Figure 4 The results of the effects of different rapid hardening sulphoaluminate cement dosages on mechanical strength and softening coefficient are shown in Figure 5 shown.

[0059] Depend on Figure 4 It can be seen that with the increase of the rapid-hardening sulphoaluminate cement content, the absolute dry density changes slightly, while the water content first decreases and then increases. When the rapid-hardening sulphoaluminate cement content reaches 8%, the water content drops to the minimum value of 6.6%.

[0060] Depend on Figure 5As the rapid-hardening sulfoaluminate cement content increases from 4% to 12%, the 28-day compressive strength of concrete first increases and then decreases, reaching 3.47 MPa, 4.67 MPa, and 3.81 MPa, respectively. This is because the addition of sulfoaluminate cement significantly accelerates early cement hydration. The hydration of the composite cementitious system of pozzolanic cement and rapid-hardening sulfoaluminate cement is essentially a chemical reaction within the pentad system of 3CaO·3Al2O3·CaSO4-2CaO·SiO2-CaSO4·2H2O-CaSO3-H2O. The gypsum in the rapid-hardening sulfoaluminate cement and the Portland cement promotes the formation of large amounts of ettringite and inhibits its transformation into calcium sulfoaluminate hydrate, leading to rapid crystallization and formation of an overlapping and interlaced skeleton structure. Furthermore, the C3S from the pozzolanic cement further participates in the hydration reaction to form CSH gel. The rapid-hardening sulfoaluminate cement promotes the hydration of the Portland cement, resulting in a synergistic effect. Ultimately, the early and mid-stage strength of the pozzolanic Portland cement-rapid-hardening sulfoaluminate cement-based ceramsite foam concrete was significantly increased. This also enabled more complete hydration of the pozzolanic Portland cement, ensuring the cement's later strength development. Aggregate and cement hydration products rapidly combined, overlapping with the foam to form a more stable pore structure, ensuring good adhesion between the foam, cement base, and aggregate, ultimately resulting in a significant increase in strength. On the other hand, as the CSA cement content exceeded 8%, the cement hydration reaction became too rapid, leading to rapid defoaming of the internal foam and the formation of larger, harmful pores and interconnected pores. This degraded the pore structure of the foam concrete and reduced its mechanical strength.

[0061] In summary, the compressive strength of ceramsite foam concrete with different cementitious materials added in different amounts under standard curing is different. The pozzolanic silicate cement-rapid-hardening sulphoaluminate cement composite cementing system composed of 8% rapid-hardening sulphoaluminate cement enables the foam concrete to obtain an appropriate hydration rate and significantly improves its 28d compressive strength.

[0062] Test Example 4 In order to explore the effect of different lithium mineral powder dosages on the basic properties of ceramsite foam concrete, the moisture content and absolute dry density of ceramsite foam concrete with lithium mineral powder dosages of 0%, 15%, 20%, 25% and 30% were tested respectively. The results are as follows: Figure 6 The results of the effects of different lithium ore powder dosages on mechanical strength and softening coefficient are shown in Figure 7 shown.

[0063] Depend on Figure 6 It can be seen that with the increase of lithium ore powder content, the water content of ceramsite foam concrete shows a trend of first decreasing and then increasing. When the content is 20%, the water content reaches the minimum value of 5.4%. When the content exceeds 20%, the water content begins to rise. In addition, due to the lightweight characteristics of lithium ore powder material, the absolute dry density decreases with the increase of content, and the fluctuation range is 678-710kg / m3 between.

[0064] Depend on Figure 7 Compared with ceramsite foam concrete containing 0% lithium ore powder, the ceramsite foam concrete containing lithium ore powder exhibited significant increases in 7-day compressive strength, increasing by 92.7%, 149%, 130%, and 80%, respectively. The 28-day compressive strength initially increased and then decreased with the addition of lithium ore powder, with the optimal lithium ore powder addition at 20%, yielding a 28-day compressive strength of 3.36 MPa. This may be due to the high lithium oxide content in this ore powder, which accelerates cement hardening and significantly improves the early-age strength of ceramsite foam concrete. However, the 7- to 28-day compressive strength is relatively low. For ceramsite foam concrete containing a composite cementitious system containing 20% ​​lithium ore powder, the moisture content of the concrete decreased significantly, the softening coefficient increased, and the water resistance of the concrete improved. However, as the addition of lithium ore powder continued, the dry density decreased while the moisture content also increased. Consequently, the compressive strength of the specimens decreased both before and after drying, and the softening coefficient also decreased significantly.

[0065] Test Example 5 During the interfacial structure test (EDS) energy spectrum analysis, a point was selected within the pores closest to the interface. The CaO / SiO2 mass ratio of hydration products within adjacent pores at the interface was determined by analysis, thereby investigating the influence of the composite cementitious system on the Ca / Si ratio of the cement paste in the interfacial region. The main hydration products in ceramsite foam concrete include CSH gel (calcium silicate hydrate), CH (calcium hydroxide), Aft (ettrakis vanadium), and Afm (monosulfur calcium sulfoaluminate). When the Ca / Si (CaO / SiO2) ratio of the hydration products is less than 2.5 and greater than 0.8, the CSH gel content in the mixture is likely to be higher. As the Ca / Si ratio exceeds 2.5, the CSH gel content begins to decrease, while the relative contents of other hydration products, such as CH and AFm, increase.

[0066] The hydration products in the adjacent pores of the interface structure area of ​​ceramsite foam concrete with 20% microspheres, 20% lithium ore powder, 8% rapid hardening sulphoaluminate cement and the control group were tested. The average values ​​of Ca / Si of each ceramsite foam concrete are as follows: Figure 8 As shown. Among them, Figure 8 In the experiment, OPC was the control group, OPC-microbeads was ceramsite foam concrete mixed with 20% microbeads, OPC-lithium ore powder was ceramsite foam concrete mixed with 20% lithium ore powder, and OPC-CSA was ceramsite foam concrete mixed with 8% rapid-hardening sulphoaluminate cement.

[0067] Depend on Figure 8It can be seen that according to the high CSH content in the range of calcium-silicon ratio of 0.8-2.5, it can be found that the CaO / SiO2 value near the cement stone interface of ordinary ceramsite foam concrete is around 2.5, and the measured CaO / SiO2 values ​​of the groups with 20% microspheres, 20% lithium mineral powder and 8% fast-hardening sulphoaluminate cement are between 0.8-2.5, indicating that CSH gel is the main component in the mixed hydration products; its value is slightly lower than that of the control group, which should be because the pre-wetting treatment of ceramsite causes liquid phase difference in the interface structure zone, and calcium ions diffuse into the pores on the surface of ceramsite rich in silicon phase.

[0068] In summary, the introduction of microspheres, mineral powder, rapid-hardening sulfoaluminate cement, and pozzolanic Portland cement into a composite cementitious system enhances the structure of the cement-cement interface in cement-cement foam concrete. This is primarily due to two factors: First, as cement hydration progresses, the relative humidity within the cement-cement foam concrete decreases. The water absorption properties of the cement increase its saturation, and the subsequent rehydration leads to an increase in the local water-cement ratio. This rehydration effect provides a beneficial supplement to the hydration reaction, making it more complete and prolonging the cement hydration process, thereby consuming excess CH and increasing the CSH content. Second, the microspheres and mineral powder participate in the secondary hydration reaction, consuming CH in the concrete, promoting the formation of hydration products, and increasing the density of the cement paste near the interface.

[0069] Although the specific embodiments of the present invention are described in detail in conjunction with the accompanying drawings, this should not be construed as limiting the scope of protection of this patent. Within the scope described by the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. Composite gelling system ceramsite foam concrete, characterized in that: The invention comprises the following components in parts by weight: 300-400 parts of gel material, 30-40 parts of river sand, 100-110 parts of shale ceramsite, 0.3-0.4 parts of polypropylene fiber, 6-8 parts of cellulose, 6-8 parts of latex powder, 6-8 parts of water reducing agent, 1-5 parts of modified foaming agent and 80-100 parts of water.

2. The composite gelling system ceramsite foam concrete according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 320 parts of gel material, 35 parts of river sand, 105 parts of shale ceramsite, 0.35 parts of polypropylene fiber, 7 parts of cellulose, 7 parts of latex powder, 7 parts of water reducing agent, 1-5 parts of modified foaming agent and 90 parts of water.

3. The composite gelling system ceramsite foam concrete according to claim 1 or 2, characterized in that: The gel material comprises the following components in parts by weight: 50-55 parts of pozzolanic silicate cement, 5-10 parts of rapid-hardening sulphoaluminate cement, 15-25 parts of microspheres and 15-25 parts of lithium mineral powder.

4. The composite gelling system ceramsite foam concrete according to claim 3, characterized in that: The particle size of the microbeads is 0.1-5 μm.

5. The composite gelling system ceramsite foam concrete according to claim 1 or 2, characterized in that: The diameter of the shale ceramsite is 1.5-2 cm, and the natural bulk density ranges from 420-450 kg / m 3 , the pre-wetting degree is 50%.

6. The composite gelling system ceramsite foam concrete according to claim 1 or 2, characterized in that: The water reducer is a polycarboxylic acid type high performance water reducer.

7. The composite gelling system ceramsite foam concrete according to claim 1 or 2, characterized in that: The modified foaming agent comprises the following components in parts by weight: 0.01 parts of gum arabic and 1 part of micron protein cement foaming agent.

8. The method for preparing composite gelling system ceramsite foam concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Mix the gel material, river sand and shale ceramsite evenly to obtain a premixed dry material; S2. Mix the cellulose, latex powder and 1 / 2 of the water, add them to the premixed dry material obtained in step S1 and stir, then add the remaining water and stir to obtain a mixture; S3. Add a water reducer to the mixture obtained in step S2, and then add polypropylene fibers. After the slurry is fluidized, continue stirring until the polypropylene fibers are evenly dispersed, thereby obtaining a gelling material mixed slurry; S4. Dilute the modified foaming agent with water to prepare foam, add the foam to the cementitious material mixed slurry obtained in step S3, stir rapidly until the foam disappears, and then let it stand and cure to a corresponding age to obtain composite cementitious system ceramsite foam concrete.

9. The method for preparing composite gelling system ceramsite foam concrete according to claim 8, wherein: In step S4, the mass ratio of the modified foaming agent to water is 1-2:35-45.

10. The method for preparing composite gelling system ceramsite foam concrete according to claim 8, wherein: In step S4, the mixture is allowed to stand for 20-30 hours at a temperature of 15-25° C. and a humidity of 93-97%.